2006
DOI: 10.1177/153537020623100101
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Interactions Between Macrophages and Leydig Cells

Abstract: The purpose of this minireview is to present information concerning the morphologic and functional relationship between testicular macrophages and Leydig cells. Although data concerning the negative influence of macrophage-derived products on testicular Leydig cells exist, this review is focused on the stimulatory influences thought to be involved in the physiologic interactions between these two diverse cell types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 70 publications
4
118
0
Order By: Relevance
“…It is important to emphasize that the structural organization of the testis may account for the integration of autocrine and paracrine factors to regulate testicular steroidogenesis and TIF characteristics and/or content. Although testosterone is an exclusive product of Leydig cells, secretory products originated from seminiferous tubule and/or Sertoli cells and/or non-steroidogenic cells in the testicular interstitium (Klinefelter et al, 1987;Saez, 1994;Hutson, 2006) could take place in regulation of TIF characteristics. Accordingly, reported changes in the TIF and testosterone content in testis could be the consequence of the complex effects of secretory contribution of the different cell types including, besides HSD3B-positive Leydig cells, also macrophages, endothelial cells, fibroblasts, peritubular cells, Sertoli cells etc.…”
Section: (A) (B) (D) (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that the structural organization of the testis may account for the integration of autocrine and paracrine factors to regulate testicular steroidogenesis and TIF characteristics and/or content. Although testosterone is an exclusive product of Leydig cells, secretory products originated from seminiferous tubule and/or Sertoli cells and/or non-steroidogenic cells in the testicular interstitium (Klinefelter et al, 1987;Saez, 1994;Hutson, 2006) could take place in regulation of TIF characteristics. Accordingly, reported changes in the TIF and testosterone content in testis could be the consequence of the complex effects of secretory contribution of the different cell types including, besides HSD3B-positive Leydig cells, also macrophages, endothelial cells, fibroblasts, peritubular cells, Sertoli cells etc.…”
Section: (A) (B) (D) (C)mentioning
confidence: 99%
“…Results of this study on Leydig cells isolated from control or Doxa-treated rats showed different effects: 19Doxa/29Doxa applications significantly increased basal/hCG-stimulated androgens production by Leydig cells ex vivo, whereas 109Doxa decreased. The discrepancy between levels of androgens in serum, TIF, testes, and those produced ex vivo by Leydig cells could be explained by the fact that isolation/ purification/stimulation of Leydig cells takes approximately 12 h when isolated Leydig cells are removed from the biologically active inhibitory and/or stimulatory paracrine compounds released from the seminiferous tubules and/or macrophages, endothelial cells, fibroblasts, peritubular cells, Sertoli cells (Klinefelter et al, 1987;Saez, 1994;Hutson, 2006). In summary, the complex structural organization of the testes and coexistence of multiple regulatory mechanisms that control testicular cells and microvasculature could provide a degree of redundancy in the maintenance of testicular steroidogenesis, a crucial component of the reproductive process.…”
Section: (A) (B) (D) (C)mentioning
confidence: 99%
“…35 The macrophages have an important function in regulating the development and steroidogenesis of Leydig cells in rats. 36 Macrophages belong to the family of antigen-presenting cells. However, testicular macrophages exhibit relatively low inflammatory responses and high immunosuppressive properties compared with the macrophages located in other tissues.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…Peptides can regulate cultured human peripheral blood mononuclear cells and macrophages, associated closely with Leydig cells and interdigitations between these two cell types in testis [11,22], to release cytokines, which could influence Leydig cell steroidogenesis [12,19]. Thus, CS and its fractions might indirectly regulate steroidogenesis of Leydig cells through a paracrine route.…”
Section: Discussionmentioning
confidence: 99%